Malta : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malta. (IMF Staff Country Reports; Country Report ;, 2021)
The fallout from the COVID-19 crisis has hit the Maltese economy hard, particularly its large tourism sector. Using fiscal buffers accumulated prior to the pandemic, the authorities have taken swift actions to support households, businesses, and the healthcare system. With the rapid rollout of COVID-19 vaccine, the economy has reopened for the summer tourism season. While the outlook is surrounded by a high degree of uncertainty, the Maltese economy is expected to rebound by 5 3/4 percent this year, up from -7 3/4 percent in 2020. The financial system has remained stable. In late June 2021, the Financial Action Task Force (FATF) put Malta under increased monitoring due to concerns about effectiveness of its anti-money laundering and combatting the financing of terrorism (AML/CFT) framework.